UPAYA PEMERINTAH INDONESIA DALAM MENANGANI ILEGAL FISHING DI PERBATASAN INDONESIA DAN FILIPINA - Mohamad Pano; Burhan Niode; Franky R. D. Rengkung (Pusat Riset dan Inovasi Nasional, 2023)
Illegal fishing still occurs in Indonesian waters, although various efforts have been made to deal with it. This illegal activity is not only a problem for Indonesia, but also a cross-country problem because the actors and activities are cross-country, and because of that, the handling of this problem must be carried out cross-country, especially through bilateral cooperation. This study aims to determine the Indonesian Government's Efforts to Handle Illegal Fishing on the Border of Indonesia and the Philippines. The lack of a defense and security system in Indonesian waters has led to the emergence of threats such as illegal exploitation and exploration of fishery products that are not reported and are not in accordance with predetermined rules carried out by foreign parties. This act of fishing activity is commonly referred to as Illegal. This research uses a descriptive-analytic research method.With data collection techniques through interviews, observation and documentation. The results of the research show that cooperation between Indonesia and the Philippines can run well if the Philippines itself is quick in responding to ideas and agreements that have been mutually agreed upon, the slow response from the Philippines itself makes the second agreement slow to process, therefore the strategy that can be carried out by Indonesia in encouraging a quick response from the Philippines itself is by discussing every collaboration that is ongoing or has expired intensively and continuously. Bilateral talks can accelerate cooperation between the two countries in a better and more advanced direction.